PERCEPTION OF BODY IMAGE OF ELDERLY PRACTITIONERS OF PHYSICAL EXERCISE (Fiep Bulletin - online, 2017)
Human aging is a biological process that happens gradually and is characterized by several changes,whether morphological, functional, biochemical and / or psychological. The changes that the elderly person presents withadvancing age influence negatively on self-esteem and self-image because society values youth as stereotype of beauty andproductivity, thus interfering in the biopsychosocial balls elderly. Objective: To analyze the effects of physical activity for bodyimage of older practitioners of gerontology fitness project "Active Life". Materials and Methods: Presenting main characteristic isthe "interpretation" of opinions where there are observations, records, correlations and description of facts, but in a way thoughwithout manipulation of observed reality. The methods used are the data collected through questionnaires, tests and systematicobservations, checking the levels of satisfaction or dissatisfaction with body shape related to the aging process and also comparethe results with other studies. The research will be developed in gerontológica fitness practitioners elderly group project "ActiveLife" the Faculdades Integradas de Patos - PB- (FIP), Patos - PB. Partial considerations: It is estimated that this positiveassessment of body image may be related to the benefits of physical exercise, as it helps in understanding the physiologicalindividuals, psychological and social needs of the elderly, favoring experience with the body for a body full image.